Review of Eastern Self-Awareness and Western Mental Structure in Mathematics Teaching - Khadka, Dambar Bahadur; Parajuli, Krishna Kanta (Journal of Musikot Campus, 2025)
Mathematics education is traditionally viewed as a domain of numerical computation and logical reasoning. However, this study reviewing the philosophical perspective by exploring mathematics as an integrative process involving cognition, emotion, self-awareness, and spirituality. Focusing on Eastern philosophical traditions—such as the Yoga Sutras, Upanishads, Bhagavad Gita, and the works of Sri Aurobindo and Western psychological theories by Vygotsky, Flavell, Damasio, Hofstadter, and Jung, the study adopts a qualitative and comparative approach through literature review and philosophical analysis. The findings reveal that Eastern perspectives emphasize mindfulness, self-realization, and inner consciousness as foundational to deep mathematical understanding, while Western frameworks highlight social interaction, metacognition, and emotional regulation as essential learning processes. This synthesis advocates for a holistic mathematics education that nurtures intellectual, emotional, cultural, and spiritual development, enabling students to engage with mathematics as a meaningful and transformative human experience.